Tidal-stream power assessment: A novel modelling approach - L. M. Flores Mateos; M. Hartnett (Energy Reports, 2020)
An alternative approach for simulating turbine array energy capture, momentum sink-TOC, was developed to improve conventional methodologies for assessing tidal-stream energy resource. The method uses a non-constant thrust force coefficient calculated based on turbines operating-conditions and relates turbine near-field changes produced by power extraction to turbine thrust forces. Momentum sink-TOC was implemented in two depth-average complex hydrodynamic models to simulate an ideal turbine lay-out to perform tidal-stream energy resource assessment. The first model solves smooth and slow flows (SSF). The second model solves rapidly varying flows (RVF). Calculation of head drops across the turbine arrays and turbine efficiencies enabled estimation of further power metrics. Tidal-stream energy resource evaluation with a tidal fence indicates that a computationally economical pre-assessment can be adequately performed using an SSF solver. However, caution should be taken when using SSF solver due to the incapacity of the model to accurately solve velocity reduction due to power extraction.
Keywords: 330; Actuator disc; Open channel flows; Shock-capturing capability; Thrust coefficient